Peran Mediasi Brand Credibility Pada Pengaruh Celebrity Endorsement Terhadap Buying Intention (Studi Kasus Pada Produk Samsung Indonesia di Samsung Shop Melalui Platform Instagram) - Hafizhah, Eltanadia Nasywa; Pardiman, Pardiman; Rachmadi, Kartika Rose (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This research aims to determine the mediating role of brand credibility on the influence of celebrity endorsement on buying intention. This research uses a quantitative approach. The sampling technique used Malhotra's formula with the results of calculating 80 samples. The data analysis technique used in this research is descriptive analysis and SEM with the Smart PLS software tool. The research results show that the mediating role of brand credibility has a significant effect on celebrity endorsement and buying intention. Keywords: Keywords: Brand Credibility, Celebrity Endorsement, Buying Intention